Peran Tes DNA terhadap Kedudukan Status Anak Li’an dari Hasil Perkawinan yang Sah Ditinjau dari Perspektif Hukum Islam dan Hukum Positif di Indonesia - Tajqia Qalbu Rahayu; Karwiyah; Adinda Putri Pertiwi (Jurnal Hukum Lex Generalis, 2022)
Divorce can occur due to allegations of adultery by the husband to his pregnant wife so as to relate to the status of his child. The husband's doubts can make him take Li'an's oath. DNA testing is commonly used for personal purposes such as the determination of guardianship of the child or the parent of the child and for a legal purpose. From the analysis, it is known that the status of the child due to Li'an's divorce according to Islamic law is the breakup of the relationship between father and son although it will be known that the child conceived by his wife is true, while according to the law is positive if there is evidence in the form of DNA tests that the child conceived by his wife is the right child of his husband, then nasab relationship with his father remains.